2016
DOI: 10.1007/s40145-015-0173-x
|View full text |Cite|
|
Sign up to set email alerts
|

Electrical and mechanical properties of (Bi,Pb)-2223 substituted by holmium

Abstract: Abstract:The effect of the partial substitution of Ca 2+ by Ho 3+ ions on the electrical and mechanical properties of the superconducting phase (Bi,Pb)-2223 was studied. Superconducting samples of the type (Bi 1.8 Pb 0.4 )Sr 2 Ca 2.1−x Ho x Cu 3.1 O 10+δ were prepared by solid-state reaction technique under ambient pressure, and characterized by means of X-ray powder diffraction (XRD) and scanning electron microscopy (SEM). The superconducting transition temperature T c and pseudogap temperature T * were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…One of the most practical technique for enhancing the microhardness of superconducting phases is the filling of voids by addition/substitution of nanoparticles. (Karara, Uzun, Kolemen, Yilmaz, & Sahin 2009) (Abdeen, et al, 2016) (Awad, 2008) (Mohammed, Abou Aly, Ibrahim, Awad , & Rekaby, 2011) (Aydin, Cakiroglu, Nursoy, & Terzioglu, 2009) (Terzioglu, 2011). The introducing of ZnO in Bi 1.84 Pb 0.34 Sr 1.91 Ca 2.03 Cu 3.06 O 10 superconductors increased the indentation hardness and the elastic modulus values as observed by Karaca et al (Karaca, Uzun, Kolemen, Yilmaz, & Sahin, 2009).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the most practical technique for enhancing the microhardness of superconducting phases is the filling of voids by addition/substitution of nanoparticles. (Karara, Uzun, Kolemen, Yilmaz, & Sahin 2009) (Abdeen, et al, 2016) (Awad, 2008) (Mohammed, Abou Aly, Ibrahim, Awad , & Rekaby, 2011) (Aydin, Cakiroglu, Nursoy, & Terzioglu, 2009) (Terzioglu, 2011). The introducing of ZnO in Bi 1.84 Pb 0.34 Sr 1.91 Ca 2.03 Cu 3.06 O 10 superconductors increased the indentation hardness and the elastic modulus values as observed by Karaca et al (Karaca, Uzun, Kolemen, Yilmaz, & Sahin, 2009).…”
Section: Introductionmentioning
confidence: 78%
“…The introducing of ZnO in Bi 1.84 Pb 0.34 Sr 1.91 Ca 2.03 Cu 3.06 O 10 superconductors increased the indentation hardness and the elastic modulus values as observed by Karaca et al (Karaca, Uzun, Kolemen, Yilmaz, & Sahin, 2009). Abdeen et al (Abdeen et al, 2016) showed that the substitution of 0.025 of holmium increased the Vickers microhardness of (Bi,Pb)-2223 superconducting phase and it had a normal indentation behavior. Awad (Awad, 2008) found that 0.6 wt% of MgO addition enhanced Vickers microhardness of (Cu 0.25 Tl 0.75 )-1234.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we focused on the variation of the porosity degree (porosity) concerning the elastic modulus of calcium oxide added Bi-2212 samples prepared under applied test forces for determining the role of applied test loads on the porosity degree that is responsible for potential engineering and industrial applications of ceramic compounds [18]. On this basis, we investigated the role of calcium oxide particles addition and applied test forces on the elastic modulus of the bulk Bi-2212 ceramic structure using the granularity degree (porosity) deduced from the Vickers microindentation hardness tests [19]. The relationship between the Young's modulus and porosity is utilized to determine the relative degrees of porosity for pure and Ca added Bi-2212 ceramics as given below [19]:…”
Section: Role Of Calcium Oxide Impurity In Elastic Modulus For Bi-221...mentioning
confidence: 99%
“…On this basis, we investigated the role of calcium oxide particles addition and applied test forces on the elastic modulus of the bulk Bi-2212 ceramic structure using the granularity degree (porosity) deduced from the Vickers microindentation hardness tests [19]. The relationship between the Young's modulus and porosity is utilized to determine the relative degrees of porosity for pure and Ca added Bi-2212 ceramics as given below [19]:…”
Section: Role Of Calcium Oxide Impurity In Elastic Modulus For Bi-221...mentioning
confidence: 99%
“…Moreover, the configuration of this phase is strongly depending on the process conditions such as sintering condition, annealing time and time of thermal processing. in this field several attempts have been made to promote the formation of the high T C phase: The accurate control of the sintering temperature and heat treatment for long periods (more than 200 hours [5][6][7], moreover synthesis atmosphere, sintering under low oxygen pressure, as well as the modification the components of a starting materials, such as, substitution for a part of Bi by combinations of Tl 0.3-x Sn x [8], part of Ca by Dy [9], part of Ca by holmium [10]. To date, an appropriate mechanism for the formation and strengthening of 2223 phase, for Bisystem as a single-phase has not yet been established.…”
Section: Introductionmentioning
confidence: 99%